PHONEMIC INTERFERENCE AND OVERREGULARIZATION IN THE /S/ AND /âˆ«/ PHONEMES REALIZATION IN FRENCH - Permana, Bagas Anugrah; Laksman-Huntley, Myrna (Universitas Pendidikan Indonesia, 2020)
One of the problems in foreign language learning is interference, a rearrangement of patterns resulting from the presence of foreign elements in the language domain (Weinreich, 2010). This research shows how and why phonemic interference of /s/ and /âˆ«/ phonemes occur from Indonesian and English although both phonemes exist in all three languages. Some interference begins from lexeme and then to phonemic level. Other faults are overregularization which is the application of regular grammatical patterns to irregular cases. This seems to support the Logical Problem of Language Acquisition which states that a student cannot correct his/her mistakes without explicit feedback from the linguistic environment (Pinker, 2004).The results of this research indicate that foreign language learning requires knowledge of non-structural elements that are outside of the language, not only following phonological, syntactic, morphological, or lexical rules (structural elements). For example, students' foreign language knowledge and cultural content in teaching materials.